GESIT EDUSEX: PENGEMBANGAN MEDIA BERBASIS GOOGLE SITES SEBAGAI MEDIA PENGETAHUAN SEKS DI KALANGAN MAHASISWA - Yulia Widayanti; Siti Rahmawati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Sex education is knowledge related to human sexuality that can be used to prevent sexual violence. It is important to be applied to the college student’s life to prevent the bias of sex education among today's young generation. It can be caused by low knowledge of sex education. The purpose of the research in this article is designed to develop the Gesit Edusex learning media in the form of e-learning media that contains sex education from various aspects by using the google site and testing the media. Integration of sex education from various aspects is intended to make sex educationable to be understood in a complex manner and is expected to suppress sexual violence. It is reviewed from the religious aspect, the health and science aspect, and the social aspect. The research method used was research and developmental research with 3D models. The research procedures consisted of ‘define’, ‘design’, and ‘development’ stages. The results of the study were in the form of sex education learning media based on the Google Site, which contained sexual knowledge from various aspects. The validation results from material experts indicated an average value of 72% with feasible criteria, the validation results from media experts indicated an average value of 65% with feasible criteria, and students’ response data indicated an average of 86% with criteria very good. Based on those data, it means that the media developed was suitable for college students to be implemented as learning media in understanding sex education.